AN IMPORTANT CONTRIBUTION TO SLAVIC PHRASEOLOGY: (A Dictionary of Croatian Animal Idioms, Ivana Vidović Bolt, Branka Barčot, Željka Fink Arsovski, Barbara Kovačević, Neda Pintarić,Ana Vasung, Zagreb, 2017) (Journal of Contemporary Philology, 2018)
Review of the Dictionary of Croatian Animal Idioms, Ivana Vidović Bolt, Branka Barčot, Željka Fink Arsovski, Barbara Kovačević, Neda Pintarić,Ana Vasung, Zagreb, 2017
Keywords: Dictionary; Croation language